Implementasi Pembelajaran Kitab Kuning dengan Pendekatan Deep Learning di Pondok Pesantren Al-Hariri Jambi - Zaharuddin M.; M. Imamuddin; Hadini; Andryadi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
We know the yellow book as a key characteristic of learning in Islamic boarding schools. In order to improve the learning of the yellow book, Islamic boarding schools must implement various learning methods, namely implementing a deep learning approach in the learning of the yellow book. This approach designs a learning process that emphasizes students' in-depth understanding of the material, and designs learning not only to memorize material, but also to instill knowledge meaningfully. To examine this study more deeply, the researcher used a descriptive qualitative research method. The data collection methods used were observation, interviews, and documentation. The data analysis techniques used in this study were qualitative analysis and descriptive analysis. The benefit of this research is to contribute to the development of yellow book learning with a deep learning approach. Based on the results of the study, it can be concluded that the deep learning approach has a very strategic role in developing the quality of yellow book learning in Islamic boarding schools by encouraging deeper conceptual understanding, critical thinking skills, and problem-solving abilities among students regarding problems that occur in society through studying and seeking the legal basis in the yellow book.